Ophthalmic Drug Delivery, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Research in ophthalmic drug delivery has developed significant advances in the few last years, and efforts have been made to develop more effective topical formulations to increase drug bioavailability, efficiency, and safety. Drug delivery to the posterior segment of the eye remains a great challenge in the pharmaceutical industry due to the complexity and particularity of the eye's anatomy and physiology. Some advances have been made with the purpose of maintaining constant drug levels in the site of action. The anatomical ocular barriers have a great impact on drug pharmacokinetics and, subsequently, on the pharmacological effect.Despite the increasing interest in efficiently reaching the posterior segment of the eye with reduced adverse effects, there is still a need to expand the knowledge of ocular pharmacokinetics that allow the development of safer and more innovative drug delivery systems. These novel approaches may greatly improve the lives of patients with ocular pathologies.